Experimental set up for the mechanical characterization of plane ITM membrane at high temperature. Issue 14 (November 2015) - Gazeau, Camille; Gillibert, Jean; Blond, Eric; Geffroy, Pierre-Marie; Richet, Nicolas
Abstract: Mixed ionic and electronic conductors (MIEC) are promising materials for ion transport membrane (ITM) based technologies. A reliable design of these membranes requires a better knowledge of their macroscopic mechanical properties. These properties are linked to the composition of membrane materials, but also in a large part to the manufacturing process. Then, the mechanical characterization set-up must allow using specimen very similar in term of manufacturing process as the final parts in. The use of the diametric compression test on thin plates is investigated here, combined with full-field measurements. Guideline for sample size, solution for classical artifact and a dedicated I-DIC algorithm are proposed. Then, Young modulus and tensile strength of seven MIEC compositions of the lanthanum-ferrite perovskite series (La(1− x ) Sr x Fe(1− y ) Ga y O3−δ, La0.5 Ba0.5 Fe0.7 Co0.3 O3−δ and La0.5 Ca0.5 Fe0.7 Co0.3 O3−δ ) were determined at room temperature and at 900 °C.